Behavior and Study of the Kinetics Aspects of Hydrothermal Leaching Conducted on Thermal Activated Products of Complex Polymetallic Secondary Sulfide Concentrate - Y. Wu; Y. Liao; H. Ma; J. Li (Archives of Metallurgy and Materials, 2025)
The utilization of complex polymetallic secondary sulfide concentrate (CPSSC) is difficult, owing to its special structure and composition. In this paper, CPSSC was firstly activated by roasting under atmosphere, followed by hydrothermal leaching under oxygen pressure with water. The mineral phase structure and morphology of the activated products and leached residues were characterized by XRD and SEM-EDS to study the leaching behavior and kinetic characteristics of copper from CPSSC. The obtained results show that the optimum conditions for hydrothermal leaching of the roasting activated products of CPSSC under oxygen pressure with water are as follows: leaching temperatures 185℃, oxygen partial pressure 0.6 MPa, liquid solid ratio 12.5:1, stirring rate 600 r/min. Under the above conditions, the iron and lead existing in the activated products were mostly transferred and remained in leached residue with the state of iron oxide and lead sulfate respectively, and the leaching rate of Cu reached 95.73%. The kinetic analysis show that the extracting of copper from the activated product by hydrothermal leaching under oxygen pressure obeys chemical reaction control model, with activation energy calculated as 41.98 kJ/mol by Arrhenius equation, and the leching kinetic equation of copper could be expressed as: 1-(1-X)1/3=0.437Po21.258w0.728e-5049.7/T t.